Analisis Yuridis Terhadap Putusan Pengadilan Tentang Penipuan Arisan Online (Studi Putusan Nomor 138/Pid.B/2023/PN TGT Versus Putusan Nomor 287K/PID/2024) : Penelitian - Mahayani Ersandy Putri; Lanna Fadilla Citra (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Online arisan fraud has become a serious threat in the digital era by exploiting supervisory loopholes and the lack of public literacy. This research juridically analyzes the Tanah Grogot District Court Decision Number 138/Pid.B/2023/PN Tgt and the Supreme Court Decision Number 287K/Pid/2024. The research results indicate a fundamental disparity in legal interpretation. The District Court decision tends to be conservative and fails to accommodate electronic evidence, acquitting the defendant as the act was deemed not to meet the elements of Article 378 of the Criminal Code. Conversely, the Supreme Court demonstrated a progressive interpretation, accepting digital evidence as valid proof, and declaring the defendant guilty. This proves that judges' understanding of information technology is crucial in deciding cases based on electronic evidence. This difference in approach demands the harmonization of the Criminal Code, the ITE Law, and digital forensic guidelines. This research recommends routine training, regulatory strengthening, inter-agency collaboration, and the application of restorative justice to strengthen law enforcement and the protection of online arisan victims.